HYDRODYNAMIC STUDY OF FREE STANDING DRILLING RISERS UNDER HURRICANE CONDITIONS - YONG , HONG YAW (2018)
Offshore structures are susceptible to damages due to a hurricane. The main subject of this thesis, free standing drilling riser (FSDR), is an innovation to the drilling riser that enables rapid disconnection prior to hurricane conditions